The Chinese banks' directors and their risk-taking behavior: A corporate governance and finance perspective. Issue 2 (6th June 2016) - Chan, Sok-Gee; Koh, Eric H.Y.; Karim, Mohd Zaini Abd
Abstract : Purpose: The purpose of this paper is to examine the impact of the directors' socioeconomic backgrounds on the risk-taking behavior of the listed commercial banks in China. Design/methodology/approach: The generalized least square method and Arellano and Bover's (1995) generalized method of moment were used to study the relationship between the directors' socioeconomic backgrounds and bank risk-taking behavior. The sample studied consists of 16 listed commercial banks in China from 2003 to 2011. Findings: It was found that smaller board sizes and higher percentage of independent directors contribute to lower risk-taking. The results also indicate that banks are better off with boards that have gender diversity, government affiliation and higher average age because they enhance problem-solving and market insights facilitate adherence to government or regulatory policies and help reduce the banks' risks. Research limitations/implications: Future studies may consider including non-public-listed banks, pre-2003 data and analyses of the agencies to which the government-affiliated directors are or were attached. Practical implications: The paper suggests that corporate governance reform initiatives with closely monitored implementation and phased liberalization contributed toward the banking industry's resilience. Implications for management include that boards of directors with better quality, sufficient independence, gender diversity, government affiliation and maturity will help reduce risks. Social implications: This study may facilitate the decision-making for the bank management and policymakers on the selection of best directors in the Chinese banking sector. The Chinese banking system serves as a plausible role model for consideration, given that four of its banks have now leapfrogged to be among the top ten largest banking institutions after the global financial crisis. Originality/value: The study covers a wide range of socioeconomic backgrounds of the board of directors which are crucial in influencing the behavior of the board in banking operations.